Innovation Persistence on Ecuadorian SMEs Growth - Simbaña-Taipe, Luis (2021)
Small and medium-sized enterprises (SMEs) are a significant part of the business network in Ecuador, as they contribute to the gross domestic product and the labor force. The aim of this research is to determine the impact of innovation persistence on the growth of Ecuadorian SMEs, through sales and employment growth variables. This phenomenon is analyzed considering two approaches: background dependence and virtuous circles of accumulation. This study evaluates a sample of 5,136 companies, during the period 2009−2014 and it uses quantile regression model (QR) for panel data. The findings show that there is no persistence for SMEs, except for high-growth companies.